Characteristic Diagnostic Clues of Metatropic Dysplasia: The Lumbothoracic Humpback with Dumbbell Appearance of the Long Bones - Guchev Z; Kalcev G; Laban N; Bozhinovski Z; Popovski N; Saveski, A; Daskalov B; Plaseska-Karanfilska D; Tasic V (Walter de Gruyter GmbH, 2018)
Metatropic dysplasia (MD) is a rare skeletal dysplasia associated with heterozygous mutations in the TRPV4 gene. We describe a 28-month-old boy with knock-knees referred for metabolic investigation suspected of carrying vitamin D-resistant rickets. He has received regular vitamin D prophylaxis at the usual dose. Laboratory investigations revealed normal values for calcium, phosphorus and alkaline phosphatase. He was short (-3.5 SDS), his mental development was normal, and he started to walk at the age of 22 months. The diagnostic clue for the diagnosis of metatropic dysplasia was the presence of the hump back in the upper lumbar and lower thoracic vertebrae, in addition to a long and narrow chest. An X-ray survey of the skeleton revealed platyspondyly, dysplastic metaphyses with dumbbell appearance of the long bones, kyphoscoliosis, and narrow and elongated thorax with short ribs. This is the first patient with MD in the Republic of Macedonia. Knock-knees were the cause of his referral, as a peculiarity of his phenotype. The very presence of the hump back, and the dumbbell appearance of the long bones distinguished the MD from other bone dysplasias with similar characteristics. We believe that the presence of those two features can shorten the path to accurate diagnosis in the crowded field of overlapping skeletal dysplasias. The diagnosis of MD in this patient was further confirmed by the discovery of the mutation c.2396C>T; p.Pro799Leu (P799L) of the TRPV4 gene.